Non-convulsive Status Epilepticus Presenting as Acute Confusional State in a Young Adult - B. D. Sharma; Amit Kumar Batra (Indian Journal of Medical Specialities)
Nonconvulsive status epilepticus (NCSE) can occur in a variety of clinical conditions and is characterized by prolonged electrographic seizures without clinically discernible seizure activity. It may be one of the most frequently missed diagnoses in patients with altered neurologic function because it is often seen in patients with other serious illnesses. For accurate diagnosis of NCSE, an alteration in baseline cognition or behavior and a concurrent epileptiform seizure pattern on electroencephalography (EEG) must be present. This case of a young adult male presented to our emergency room with an acute onset of confusional state and behavioral changes with no clue for its etiology on initial clinical or after routine investigations including CT brain until EEG picked up continuous epileptic discharges. He responded dramatically to antiepileptic drugs without any recurrence during follow-up of 4 months. Many cases like this are being diagnosed with the use of continuous EEG monitoring (cEEG) in Neurological Intensive Care Units. The advent of cEEG is instrumental in the diagnosis as well as monitoring the response to treatment of this condition with antiepileptic drugs. Increased awareness and a high index of suspicion are needed for timely diagnosis of NCSE if a patient presents with acute onset of unexplainable cognitive or behavioral change of at least 30–60 min duration. Patients with NCSE need to be managed exactly as convulsive SE, using EEG as a guide rather than clinical observations as the determinant of response to treatment.